Trichinella pseudospiralis in a wolverine (Gulo gulo) from the Canadian North - Sharma, Rajnish; Thompson, Peter; Elkin, Brett; Mulders, Robert; Branigan, Marsha; Pongracz, Jodie; Wagner, Brent; Scandrett, Brad; Hoberg, Eric; Rosenthal, Benjamin; Jenkins, Emily (Zenodo, 2019)
Sharma, Rajnish, Thompson, Peter, Elkin, Brett, Mulders, Robert, Branigan, Marsha, Pongracz, Jodie, Wagner, Brent, Scandrett, Brad, Hoberg, Eric, Rosenthal, Benjamin, Jenkins, Emily (2019): Trichinella pseudospiralis in a wolverine (Gulo gulo) from the Canadian North. International Journal for Parasitology: Parasites and Wildlife 9: 274-280, DOI:10.1016/j.ijppaw.2019.06.005, URL: http://dx.doi.org/10.1016/j.ijppaw.2019.06.005